(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article scientifically analyzes the process of revolutionary transformation of the organization and expansion of retail and corporate banking services by commercial banks to a digital business model. The study examines the initiative of the state regulator of the British banking system in 2015 to use open API standards, technological innovations in the activities of commercial banks, mobile banking, “super-app” solutions, P2P payments, and the use of big data technologies. It also deeply studies the historical stages of the activities of commercial banks, the three successive stages of digitalization - the development of customer relationships through digital channels, the adaptation of technological infrastructure, and the implementation of strategic changes. Recommendations were developed for the modernization of the banking system in Uzbekistan, the implementation of international transformation processes, the widespread use of modern mobile and digital technologies, the diversification of banking services, and increasing security. This research creates a theoretical and practical basis for adapting banking activities to the digital ecosystem, developing services focused on customer needs, and ensuring sustainable financial growth.